Novel Characteristics of Immune Responsive Protein IRP30 in the Bumble Bee Bombus lantschouensis (Hymenoptera: Apidae). Issue 2 (27th March 2020) - Dong, Jie; Wu, Jie; Han, Lei; Huang, Jiaxing; Wang, Deqian
Abstract: Immune responsive protein 30 (IRP30) is a Hymenoptera-specific protein first identified from honey bee hemolymph in response to bacterial infection. However, its function remains elusive. Here, we cloned the full-length IRP30 gene and clarified its expression pattern in the bumble bee Bombus lantschouensis (Vogt). The full-length IRP30 gene measures 1443 bp and contains two exons and one intron. The length of the cDNA is 1082 bp, including a 36-bp 5′-UTR and a 218-bp 3′-UTR, and it encodes a putative protein of 275 amino acids. As expected, the sequence of the B. lantschouensis IRP30 protein was clustered with the bumble bee group, which appeared as a single clade next to honey bees. The family shared similar conserved protein domains. Moreover, bumble bee IRP30 belongs to a recently diverged clade that has four leucine-rich repeat (LRR) conserved domains. IRP30 is highly expressed in the worker caste, during pupal developmental stages, and in the head and thorax tissues. Interestingly, its expression increases 20- to 90-fold when female bumble bees ( B. lantschouensis ) and honey bees ( Apis mellifera L. ) begin laying eggs. Overall, based on the expression of IRP30 during development and egg laying in female bumble bees, this protein not only responds to immune challenge but also may play an important role in metamorphosis and reproduction.